Application of Social Cognitive Theory as a Predictor of Quitting E-Cigarette Use among College Students - Kintan Candra; Bhisma Murti; Revi Gama Hatta Novika; Hanung Prasetya; Setyo Sri Rahardjo (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Social Cognitive Theory was selected as the framework of this study because it can be used to explain, prevent, or reduce risky behaviors such as e-cigarette use. This study aimed to analyze and predict the behavior of quitting e-cigarettes through social cognitive theory among students. Subjects and Method: This study was conducted in October-November 2024 with a sample of 200 students. The study was a cross-sectional study with study subjects selected using the fixed disease sampling technique. The dependent variable was the behavior of quitting using e-cigarettes. And the independent variables were knowledge, self-regulation, outcome expectation, self-efficacy, and observational learning. Results: Quitting e-cigarettes was directly influenced by self-efficacy (b= 1.63; CI 95%= 0.93 to 2.33; p< 0.001) and outcome expectation (b= 0.82; CI 95%= 0.15 to 1.50; p= 0.017). Self-efficacy was directly influenced by knowledge (b= 0.94; CI 95%= 0.32 to 1.57; p= 0.003). Likewise, the outcome expectation was influenced by knowledge (b= 0.90; CI 95%= 0.28 to 1.53; p= 0.004). Knowledge was influenced by observational learning (b= 1.28; CI 95%= 0.65 to 1.92; p< 0.001). And self-regulation was influenced by the decision to quit using e-cigarettes (b=0.94; CI 95%= 0.37 to 1.51; p=0.001). Conclusion: This study concludes that constructs in Social Cognitive Theory can be used as a predictor of quitting e-cigarettes.